African American Women, Racism and Triple Oppression - Chapagain, Rajendra Prasad (Interdisciplinary Journal of Management and Social Sciences, 2020)
African American women have been made multiple victims: racial discrimination by the white community and sexual repression by black males of their own community. They have been subjected to both kind of discrimination - racism and sexism. It is common experience of black American women. Black American women do have their own peculiar world and experiences unlike any white or black men and white women. They have to fight not only against white patriarchy and white women's racism but also against sexism of black men within their own race. To be black and female is to suffer from the triple oppression- sexism, racism and classicism.